An enhanced fast fundamental frequency estimator for three-phase electric aircraft grid. (15th June 2022) - Jula, Bhumaiah; Jarial, Raj Kumar; Verma, Anant Kumar; Roncero-Sánchez, Pedro; Guerrero, Josep M.; Davi Curi Busarello, Tiago; Ahmed, Hafiz
Abstract: This article proposes a robust and enhanced three-phase fundamental frequency estimation algorithm for the electric aircraft grid. Unlike conventional frequency-locked loops, the digital signal processing technique-based frequency estimator proposed relies on the storage of five consecutive samples of the fundamental grid voltage signal. Furthermore, the ability to successfully operate at a low sampling frequency, i.e. 8 kHz, makes it sufficiently attractive as regards reducing the memory storage in a low-cost real-time controller. The proposed frequency estimator can additionally eliminate the negative effects of the DC-offset and the fundamental negative sequence components present in the grid signal without any additional effort. Also, the tuning efforts are reduced for the frequency variation range of 350–900 Hz owing to the existence of a single tuning gain parameter. The proposed algorithm has also been found to have a fast dynamic response, which has been experimentally validated through the use of a real-time digital controller. Highlights: Rapid detection of the fundamental frequency of an electric aircraft grid. Phase-locked loops (PLLs) and Frequency-locked loops (FLLs) are complex solutions. Open-loop frequency estimator performs well in a wider frequency range (350-900 Hz). Lower sampling frequency helps to eliminate the costly hardware. Immunity against DC-offset may yield better accuracy in the estimate of frequency. Reduced sensitivity towards fundamental negative sequence component of grid signal. Higher noise rejection abilities and reduced number of control parameters.